Genomic insights into the antimicrobial and anticancer potential of streptomyces sp.A1-08 isolated from volcanic soils of Mount Mayon, Philippines - Oliveros, Kristel Mae P.; Rosana, Albert Remus R.; Montecillo, Andrew D.; Opulencia, Rina B.; Jacildo, Arian J.; Zulaybar, Teofila O.; Raymundo, Asuncion K. (2021)
"Antimicrobial resistance (AMR) poses a global and developmental threat to humanity. The rapid emergence and spread of drug-resistant pathogens resulted in the ineffective use of currently available antibiotics. Therefore, there is a need to continue searching for additional sources of antibiotics, such as actinomycetes, which can potentially harbor unique and effective secondary metabolites. Furthermore, it is interesting to consider poorly explored environments like volcanoes, which can be potential sources of drug leads for medically important natural products. This study reports the antimicrobial activity of actinomycetes isolated from volcanic soil samples collected from Mount Mayon, Albay, Philippines"-title page.
Includes bibliographical references.
Keywords: Actinobacteria; Antibiotics -- Philippines -- Bikol; Volcanic soils -- Philippines -- Bikol